2015
DOI: 10.5851/kosfa.2015.35.1.58
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Egg Shell Membrane Hydrolysates on UVB-radiation-induced Wrinkle Formation in SKH-1 Hairless Mice

Abstract: This study was conducted to examine the effect of egg shell membrane hydrolysates (ESMH) on wrinkle, UV, and moisture protection for cosmetic use. ESMH were fragmented as whole ESMH (before fractioning), Fraction I (> 10 kDa), Fraction II (3-10 kDa), and Fraction III (< 3 kDa). In order to test whether fractionated ESMH can be used for functional cosmetic materials, we examined not only the level of hyaluronic acid and collagen production, but also the MMP-1 activity using a HaCaT and CCD-986Sk cell line. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 32 publications
1
19
1
Order By: Relevance
“…Moreover, treatment with eggshells has previously shown a positive effect on skin parameters such as pigmentation and hydration. These effects seem to be mediated by an increase of collagen and HA levels, a reduction of matrix metalloproteinase activity, inhibition of collagenase and elastase, and inhibition of skin inflammation (Yoo et al 2014;Yoo et al, 2015). Although our results showed a tendency toward skin pigmentation reduction, the difference was not statistically significant.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Moreover, treatment with eggshells has previously shown a positive effect on skin parameters such as pigmentation and hydration. These effects seem to be mediated by an increase of collagen and HA levels, a reduction of matrix metalloproteinase activity, inhibition of collagenase and elastase, and inhibition of skin inflammation (Yoo et al 2014;Yoo et al, 2015). Although our results showed a tendency toward skin pigmentation reduction, the difference was not statistically significant.…”
Section: Discussioncontrasting
confidence: 74%
“…Eggshell membrane, an organic substance, is known to increase cellular activity, increase collagen production, slow skin aging, and reduce the detrimental effects of damage from UV light and inflammation (Candilish & Scougall,1969;Yoo et al, 2014;Yoo et al, 2015). The objective of this research was to study the effectiveness of Ovoderm, composed of egg membrane, on skin biophysical parameters, such as elasticity, pigmentation, and hydration, related to cutaneous aging.…”
Section: Introductionmentioning
confidence: 99%
“… 16 Of specific interest for the research reported in this article, an earlier study showed that the application of an extract of soluble EM peptides diminished UV-B radiation-induced wrinkle formation in a model of hairless mice, linked to a dose-dependent inhibition of collagenase and also linked to an increase in synthesis of collagen and hyaluronic acid. 17 The aim of this study was to evaluate the effects of soluble EM peptides when applied topically on human skin and to explore specific mechanisms of action pertaining to skin cell matrix deposition and free radical protection at the cellular level.…”
Section: Introductionmentioning
confidence: 99%
“…ESM-P has been reported to have a skin-moisturising effect and to ameliorate knee joint pain [5, 6]. Similar effects have been reported for hyaluronic acid [19, 20].…”
Section: Discussionmentioning
confidence: 80%
“…Eggshell membranes have been used as carbon dioxide and heavy metal absorbers [2, 3], and also in sauces such as soy sauce [4]. They have also been reported to have a skin-moisturising effect and to ameliorate knee joint pain [5, 6]. To clarify these and other potential health functions, it is important to elucidate the action mechanisms of eggshell membrane protein (ESM-P).…”
Section: Introductionmentioning
confidence: 99%